Evaluation of the synergistic effect of eravacycline and tigecycline against carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae - Yu-Shan Huang; Jia-Ling Yang; Jann-Tay Wang; Wang-Huei Sheng; Chia-Jui Yang; Yu-Chung Chuang; Shan-Chwen Chang (Elsevier, 2024)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a substantial healthcare challenge. This study assessed the in vitro efficacy of selected antibiotic combinations against CRKP infections. Methods: Our research involved the evaluation of 40 clinical isolates of CRKP, with half expressing Klebsiella pneumoniae carbapenemase (KPC) and half producing Metallo-β-lactamase (MBL), two key enzymes contributing to carbapenem resistance. We determined the minimum inhibitory concentrations (MICs) of four antibiotics: eravacycline, tigecycline, polymyxin-B, and ceftazidime/avibactam. Synergistic interactions between these antibiotic combinations were examined using checkerboard and time-kill analyses. Results: We noted significant differences in the MICs of ceftazidime/avibactam between KPC and MBL isolates. Checkerboard analysis revealed appreciable synergy between combinations of tigecycline (35%) or eravacycline (40%) with polymyxin-B. The synergy rates for the combination of tigecycline or eravacycline with polymyxin-B were similar among the KPC and MBL isolates. These combinations maintained a synergy rate of 70.6% even against polymyxin-B resistant isolates. In contrast, combinations of tigecycline (5%) or eravacycline (10%) with ceftazidime/avibactam showed significantly lower synergy than combinations with polymyxin-B (P < 0.001 and P = 0.002, respectively). Among the MBL CRKP isolates, only one exhibited synergy with eravacycline or tigecycline and ceftazidime/avibactam combinations, and no synergistic activity was identified in the time-kill analysis for these combinations. The combination of eravacycline and polymyxin-B demonstrated the most promising synergy in the time-kill analysis. Conclusion: This study provides substantial evidence of a significant synergy when combining tigecycline or eravacycline with polymyxin-B against CRKP strains, including those producing MBL. These results highlight potential therapeutic strategies against CRKP infections.